Service Quality and Customer Loyalty in Islamic Banking: A Systematic Literature Review of the Mediating Role of Customer Satisfaction - Rena Gusmaniar; Muhammad Iqbal Fasa; Hanif Hanif; Moh. Mukri; Rahmat Fajar Ramdani (Lentera Ilmu Nusantara, 2026)
Customer loyalty remains a critical challenge for Islamic banks in an increasingly competitive and digitalized financial environment. Although service quality has been widely recognized as an important determinant of customer loyalty, previous studies have reported inconsistent findings regarding the direct relationship between service quality and customer loyalty. Therefore, this study aims to systematically review the existing literature on the relationship between service quality and customer loyalty in Islamic banking, with particular emphasis on the mediating role of customer satisfaction. This study employs a Systematic Literature Review approach by examining relevant international journal articles published between 2015 and 2025. The literature was identified from major academic databases, including Google Scholar, Scopus, Web of Science, Emerald Insight, and ScienceDirect, and selected based on predetermined inclusion and exclusion criteria. The selection process focused on studies discussing service quality, customer satisfaction, customer loyalty, and mediation in the context of Islamic banking. The findings indicate that service quality consistently has a positive influence on customer satisfaction, while customer satisfaction significantly contributes to customer loyalty. The review further reveals that customer satisfaction serves as the primary mechanism through which service quality affects customer loyalty. In addition, recent evidence highlights the growing importance of digital service quality and Sharia compliance in shaping customer satisfaction and loyalty. This study concludes that improving service quality alone is insufficient to strengthen customer loyalty unless it generates customer satisfaction. Therefore, Islamic banks should prioritize customer satisfaction as a strategic objective to build sustainable customer loyalty and maintain long-term competitiveness.